Development of car fragrance from essential oils of pandan leaves - Nurul Ain Md Nor (2014)
This research intent to extract essential oils from the pandan leaves and to develop a car fragrance from pandan leaves extract. To obtain data, this research employed an experiment. The experiment involved steam distillation method. We used 500g of pandan leaves in a 500mL round bottomed flask as the distilling pot. The round bottom flask was placed in a heating mantle with temperature at 2 °C. Enough water was added so that the distilling pot is about 2/3 full. Besides that, a small hot plate was used as the heat source. A Claisen connecting tube was used to connect the distilling pot to the distillation head. The Claisen was wrapped with the parafilm to keep it hot during the distillation. The heat was adjusted so the distilling rate equals about 20 drops per minute. The overall results indicated about 150mL of distillate were collected and 0.75 mL of essential oils was obtained. The essential oils was tested by using filter paper that absorbed the pandan fragrance in was placed in Petri dish to test the longer of the smell retains. For further research in this scope of study we could analyze the compound responsible for insect repellent properties because pandan leaves can act as insect repellent.